2021
DOI: 10.1016/j.annonc.2021.08.1926
|View full text |Cite
|
Sign up to set email alerts
|

1325P Checkpoint inhibitor monotherapy in potentially study-eligible or non-study-eligible NSCLC patients in the German CRISP registry real-world cohort (AIO-TRK-0315)

Abstract: therefore a feasible tool is urgently needed to predict the patients who might benefit from ICIs in clinical practice. Methods:We enrolled 76 patients with advanced NSCLC and treated them with ICIs in three independent cohorts. Using transcriptome data analysis of a training set (n¼35), we constructed a predictive signature consisting of immune-related gene pairs (IRGPs). The predictive signature was first validated in the testing set (n¼20) and then validated in an independent cohort containing 19 patients re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Indeed these subgroups differed significantly regarding median OS, with “potentially trial-eligible” patients showing a significantly longer median OS of 26.2 months, which was then comparable to the OS reported in RCTs [ 8 ]. We also evaluated the impact of trial eligibility on treatment, survival, and patient-reported outcome of patients with advanced NSCLC treated with pembrolizumab monotherapy in first line in routine care, seeing that almost 50% of the patients would not have met eligibility criteria for RCTs [ 62 ]. These findings are of substantial relevance for physicians discussing outcomes with their patients.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed these subgroups differed significantly regarding median OS, with “potentially trial-eligible” patients showing a significantly longer median OS of 26.2 months, which was then comparable to the OS reported in RCTs [ 8 ]. We also evaluated the impact of trial eligibility on treatment, survival, and patient-reported outcome of patients with advanced NSCLC treated with pembrolizumab monotherapy in first line in routine care, seeing that almost 50% of the patients would not have met eligibility criteria for RCTs [ 62 ]. These findings are of substantial relevance for physicians discussing outcomes with their patients.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that trial-ineligible metastatic NSCLC patients treated with pembrolizumab monotherapy had significantly worse outcomes than trial-eligible patients. 12 Another difference between clinical trials and everyday practice is treatment duration. In KEYNOTE-189, the maximal duration of pembrolizumab was 2 years (35 cycles), whereas the EMA authorized continuation of pembrolizumab after this date.…”
Section: Introductionmentioning
confidence: 99%